Integração de métodos elétricos, eletromagnéticos e aerofotogrametria para prospecção hidrogeológica em ambiente fissural no município de Cedro-CE, Brasil - Alvite, Eduardo Nunes Capelo (2022)
The semi-arid Domain of the Northeast of Brazil, where the natural and periodic phenomenon of drought occurs, the fissural system predominates and is recognized for its low cost/benefit ratio related to the construction of tubular wells and the use of groundwater. Therefore, this research aimed to improve prospecting more effectively in the exploitation of these resources. To achieve this, wells historical data, geological and structural data, integrated geophysical methods (resistivity and electromagnetic) and remote sensing with drone were used. The analysis allowed to establish minimum recommended quantities in relation to the research area. The dipole-dipole and Wenner-Schlumberger arrays were better suited, with a maximum electrode spacing of 10 meters. These results integrated with the structural geology showed the features related to the exploration failures of the existing wells, as well as the successful wells, associated with brittle structures found in the area. This methodology made it possible to analyze different responses and, thus, define a set of basic procedures necessary for the location of tubular wells in these regions with greater accuracy.